Bullous pemphigoid associated with the use of nivolumab in a patient with metastatic melanoma: a case report. - Miranda, Diego Lopes Paim; Alves, Leilah Andrade; Mata, Dyonatas Rodrigues da; Pinheiro, Nathanael; Silva, Anete Olivieri Pessoa da; Landeiro, Luciana Castro Garcia (Brazilian Journal of Oncology, 2020)
Benefits of immunotherapy within modern oncology are evident, especially when evaluating survival, morbidity and systemic effects in the treatment of neoplastic tumors. However, adverse events have been described in association with checkpoint inhibitors. We aim to describe a case of bullous pemphigoid in a patient with metastatic melanoma treated with nivolumab. A 62-year-old male diagnosed with metastatic melanoma and BRAF mutation who underwent surgical resection started nivolumab and during the 40th cycle presented dermatological lesions compatible with bullous pemphigoid. After confirmation with biopsy, corticosteroid therapy was adopted and remission of the lesions was observed followed by relapse after immunotherapy reintroduction. Even though checkpoint inhibitors express several advantages over conventional systemic agents, these drugs seem to exert toxic effects that may manifest as skin lesions. Bullous pemphigoid diagnosis, which requires careful clinical investigation, should be considered when patients present dermatologic symptoms after treatment with nivolumab.
Keywords: Pemphigoid; Bullous; Nivolumab; Melanoma